Auditoria en seguridad vial al tramo la Paila – Armenia Km 44+000 al Km 50+000 del departamento del Quindío (2022)
The purpose of this investigation was to carry out an ASV of some of the elements that make up the road, which allow determining its estatus in front of the users who pass through it, in the section between Km 44 to Km 50, La Paila - Armenia.